2019
DOI: 10.1080/21623945.2019.1693747
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte epigenetic alterations and potential therapeutic targets in transgenerationally inherited lean and obese phenotypes following ancestral exposures

Abstract: The incidence of obesity has increased dramatically over the past two decades with a prevalence of approximately 40% of the adult population within the United States. The current study examines the potential for transgenerational adipocyte (fat cell) epigenetic alterations. Adipocytes were isolated from the gonadal fat pad of the great-grand offspring F3 generation 1-year old rats ancestrally exposed to DDT (dichlorodiphenyltrichloroethane), atrazine, or vehicle control in order to obtain adipocytes for DNA me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 110 publications
1
18
0
Order By: Relevance
“…This is partly in accordance with Bravo’s study from 2017, where higher levels of 4,4 DDT (4,4 DDE composed >90% of the DDT metabolites in the study [ 13 ]; the same proportion as in our material) were found to increase gestational age as well as birth weight and length. Bravo’s findings are supported by laboratory studies showing that DDT exposure increased adipogenesis in vitro [ 19 ] and obesity in rats [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 80%
“…This is partly in accordance with Bravo’s study from 2017, where higher levels of 4,4 DDT (4,4 DDE composed >90% of the DDT metabolites in the study [ 13 ]; the same proportion as in our material) were found to increase gestational age as well as birth weight and length. Bravo’s findings are supported by laboratory studies showing that DDT exposure increased adipogenesis in vitro [ 19 ] and obesity in rats [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 80%
“…It has been proposed that the effects of DDT exposure in adipocytes on the offspring from DDT-exposed rats may be significantly mediated by DNA methylation changes affecting adipogenesis regulation and metabolic functioning [86].…”
Section: Dichlorodiphenyltrichloroethane (Ddt)mentioning
confidence: 99%
“…Epigenetic mechanisms regulate chromatin structure and gene expression patterns which impact DNA/RNA methylation, and histone changes can modulate host immune responsiveness 75 . Obesity drives DNA methylation of differential regions in adipocytes 76 . Whether viral pathogens (e.g., influenza and SARS‐CoV‐2) trigger type I IFN axis responses in adipocytes and impact adipocyte DNA methylation remains to be defined.…”
Section: Adipocyte Functionmentioning
confidence: 99%